THE EFFECT OF TAX KNOWLEDGE AND TAXPAYER AWARENESS ON INDIVIDUAL TAXPAYER COMPLIANCE IN THE SUBMISSION OF PT BOBA INDAH’S ANNUAL TAX RETURN IN 2024 - Ade Sri Mulyani; Asrah Tandirerung Ranteallo; Niken Herawati (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This research aims to contribute tax knowledge, taxpayer awareness, and add insight in the application to individual taxpayer compliance with employees at PT Boba Indah. The study population includes all individual taxpayers in the company, using a nonprobability sampling method that produces a sample of 30 taxpayers. The data analysis method used was multiple linear regression analysis and hypothesis testing using the SPSS 25 program. The results of the study show that tax knowledge and taxpayer awareness have a positive and significant influence on the compliance of individual taxpayers. The implication of this study is that the Directorate General of Taxes can strive to improve education, socialization, training, and improvement programs of the e-filing system to increase the level of taxpayer compliance in submitting annual tax returns. Thus, it can be expected that the implementation of this strategy will have a positive impact in achieving the goal of increasing overall taxpayer compliance.